Effect of Tetraploid Wheat a Novel Source to expand genetic Base in Durum Wheat - Jabbour, Yaman Judat; Hakim, Mohammad Shafik; Bassi, Filippo M.; Al- Yossef, Abdallah; Saleh, Maysoun M; Shaaban, Ahmad Shams Al- Dien (Journal of agricultural, environmental and veterinary sciences, 2022)
Formation a new genetic variation is the principal procedure in breeding programs, and due to the narrow genetic base of many durum wheat varieties, new genetic recourses had to be introduced, hence the primitive wheat is considered the most promising source of novel genes. Here, study was carried out during two seasons 2017/2018- 2018/2019 at Scientific Agriculture Research Center in Aleppo/Syria to formation a new genetic base in durum wheat parents planted in first season in AL- sofera location five of them were primitive wheat 3 genotypes of T.dicoccum one genotypes of T.carthlicum and one genotype of T.polonicum which used as male parents while four cultivated varieties Bohuth9, Cahm9, Bohouth5, Cham5 used as female parents crossing was done using North Carolina II design to produce of 20 crosses groups hybrids and their parents planted in second season in Randomized Complete Block Design (RCBD) with two replications in Humeima station under supplemental irrigation condition data recorded for phenological traits (No. of days to heading, No. of days to maturity and grain filling period) morphological traits (plant height, awn length, peduncle length and spike length) grain yield and its components (thousand kernels weight, number of grain per spike) results showed significant differences among genotypes for all traits dominance gene action controlled grain filling period and grain yield whereas rest traits were controlled by additive gene action broad sense heritability was high for all traits whereas heritability in narrow sense was mid for grain filling period and grain yield and high for the rest of traits a high value for expected genetic advance associated with high narrow sense heritability recorded for thousand kernels weight, Awn length and peduncle length a positive significant genotypic and phenotypic correlation recorded between grain yield with thousand kernels weight, number of grain per spike the path coefficient analysis revealed the number of grain per spike was the most traits effect in grain yield as for indirect effects the peduncle length was the most traits effect in grain yield through the number of grain per spike.
Keywords: Durum Wheat; Interspecific Hybrids; North Carolina I I; Primitive Wheat